Evaluation of the efficacy of intramuscular versus intramammary treatment of subclinical Streptococcus agalactiae mastitis in dairy cows in Colombia (2015)
ABSTRACT: A randomized controlled trial was performed in 17 Colombian dairy herds to determine the cure risk among cows subclinically infected with Streptococcus agalactiae exposed to 2 antibiotic therapies. Composite milk samples were collected before milking at the onset of the trial (pretreatment) and 2 subsequent times over a period of approximately 63 d. The intramammary application (IMM) of ampicillin-cloxacillin was compared with the intramuscular application (IM) of penethamate hydriodide, and cure risks after an initial and retreatment application were assessed. Cure risk after the initial treatment was higher (82.4%) for the IMM treatment than for IM therapy (65.8%). However, no difference was observed in the cure risk of refractory cases after retreatment (IMM=52.6% vs. IM=51.2%). The cumulative cure risk (both initial and retreatment) was 90.4 and 82.9% for the IMM and IM products, respectively. A 2-level random effects logistic model that controlled for pretreatment cow-level somatic cell count, indicated that IM treatment (odds ratio=0.37) had a lower cure risk than IMM and a tendency for a lower cure risk with increasing baseline somatic cell count. Our findings suggest that both products and administration routes can reduce the prevalence of S. agalactiae in affected herds, but the IMM product had a better efficacy in curing the infection. In addition to the treatment protocol, the cow somatic cell count should be considered when making management decisions for cows infected with S. agalactiae.